2021
DOI: 10.1093/ofid/ofab610
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Cryptosporidiosis in Transplant Recipients: Review of the Literature and Presentation of a Renal Transplant Patient Treated With Nitazoxanide, Azithromycin, and Rifaximin

Abstract: Cryptosporidium is a major cause of diarrheal disease worldwide, including chronic disease in malnourished children and patients with AIDS. There are increasing reports of cryptosporidiosis in transplant patients, especially from middle-income countries. The literature on treatment of cryptosporidiosis in transplant patients was reviewed and included no controlled trials, but only small case series. Nitazoxanide, azithromycin, spiramycin, and combination therapies have been used, but none are consistently effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 38 publications
0
14
0
1
Order By: Relevance
“…Complete resolution of diarrhea as well as elimination of the parasite has been reported in immunosuppressed children and adults suffering from cryptosporidiosis after dual therapy with azithromycin and nitazoxanide ( Legrand et al., 2011 ; Bakliwal et al., 2021 ; Dupuy et al., 2021 ). Additionally, triple therapy involving azithromycin, nitazoxanide, and paromomycin or rifaximin led to complete clinical and parasitological cure with no relapse in renal transplant patients ( Hong et al., 2007 ; Tomczak et al., 2022 ). Another study successfully treated cryptosporidiosis in a pediatric renal transplant patient using a triple therapy consisting of spiramycin, nitazoxanide, and paromomycin ( Acikgoz et al., 2012 ).…”
Section: Treatment Options In Humans and Animals: The Past And Curren...mentioning
confidence: 99%
See 1 more Smart Citation
“…Complete resolution of diarrhea as well as elimination of the parasite has been reported in immunosuppressed children and adults suffering from cryptosporidiosis after dual therapy with azithromycin and nitazoxanide ( Legrand et al., 2011 ; Bakliwal et al., 2021 ; Dupuy et al., 2021 ). Additionally, triple therapy involving azithromycin, nitazoxanide, and paromomycin or rifaximin led to complete clinical and parasitological cure with no relapse in renal transplant patients ( Hong et al., 2007 ; Tomczak et al., 2022 ). Another study successfully treated cryptosporidiosis in a pediatric renal transplant patient using a triple therapy consisting of spiramycin, nitazoxanide, and paromomycin ( Acikgoz et al., 2012 ).…”
Section: Treatment Options In Humans and Animals: The Past And Curren...mentioning
confidence: 99%
“…But data from randomized controlled trials is required to support these results given the self-limiting nature of the disease. Nevertheless, increasing evidence has demonstrated that combination therapy achieves better clinical and microbiological resolution rates than monotherapy for the treatment of cryptosporidiosis in immunocompromised patients ( Maggi et al., 2000 ; Bhadauria et al., 2015 ; Lanternier et al., 2017 ; Bakliwal et al., 2021 ; Tomczak et al., 2022 ).…”
Section: Treatment Options In Humans and Animals: The Past And Curren...mentioning
confidence: 99%
“…Disease symptoms are selflimiting in immune-competent animals and humans. However, in immune-compromised individuals (14,15), the infection can be life-threatening, exacerbated by a deficiency in effective therapies (15,16). To date, there are no effective vaccines due to the incomplete understanding of the host immune response to the parasite infection (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…As for the treatment of C. parvum infection, it does not have an effective treatment directly, except for (NTZ) Nitazoxanide which is proven by the World Health Organization, but it is not effective for people with immunodeficiency, and many anti-Cryptosporidiosis compounds have been used, but they did not give positive results. Effective and did not kill the Oocyst permanently in a record time, including Metronidazole, Azithromycin, Paromomycin [7] ISSN: 2583-4053 Volume-1 Issue- From recent studies, Nullscript was identified as a compound that has a growth inhibitory effect, and was less toxic to host cells, Nullscript was able to significantly reduce the release of Oocyst in mice infected with C. parvum [8]…”
Section: Introductionmentioning
confidence: 99%